Documentário Copa do Mundo Marcílio Dias: 55 anos de história - SILVA, Emerson Real (Universidade Federal do Amapá, 2022)
This paper reports the elaboration process of the documentary "Copa do Mundo Marcílio Dias: 55 anos de história." ratified as a product of an experimental project of the Journalism Course of the Federal University of Amapá. The narrative presents the history of the Marcílio Dias Soccer World Cup event, which is part of Macapá's history, held for 55 years (1962-2017) at the Praça da Nossa Senhora da Conceição, in the capital, from the point of view of characters intertwined with the tournament, such as journalists, former players, narrators, entrepreneurs, and neighborhood residents. The documentary has 29 minutes and 17 seconds and was filmed in the second half of 2017 and January 2018.